2017
DOI: 10.1017/thg.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Familial and Special Twin Influences on Cigarette Use Initiation

Abstract: Background Shared experiences within families play an important role in the initiation of cigarette use among adolescents. Behavioral genetic studies using various samples have implicated that the shared environment that twins experience is an important source of influence on whether adolescents initiate cigarette use. Whether the special twin environment, in addition to the shared environment, contributes significantly to making twin siblings more similar in cigarette initiation and whether the influence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Because h 2 is often derived from twin studies, it is important to evaluate whether the environment specific to twins (compared to non‐twin siblings) confounds the calculation of heritability. Similar to studies of physiological traits (Andrew et al ., ), a recent study found no evidence that the unique environment of twins contributed to the heritability of smoking initiation (Bares et al ., ).…”
Section: Heritabilitymentioning
confidence: 97%
“…Because h 2 is often derived from twin studies, it is important to evaluate whether the environment specific to twins (compared to non‐twin siblings) confounds the calculation of heritability. Similar to studies of physiological traits (Andrew et al ., ), a recent study found no evidence that the unique environment of twins contributed to the heritability of smoking initiation (Bares et al ., ).…”
Section: Heritabilitymentioning
confidence: 97%